PENGARUH KONSTRUKSI SOSIAL BUDAYA TERHADAP KETERWAKILAN POLITIK PEREMPUAN DI PROVINSI JAMBI - Sutri Destemi Elsi; Riri Maria Fatriani; Rahman; Maratun Saadah (Halu Oleo University, 2022)
This paper discusses the influence of socio-cultural construction on women's political representation in Jambi Province. Women continue to be underrepresented in the public sphere, particularly in politics. In three districts in Jambi Province, namely Merangin Regency, Kerinci Regency, and Sungai Penuh City, there is no representation of women in the 2019 election results. This study was carried out using a descriptive quantitative method, which began by mapping the indicators of socio-cultural construction. According to the findings, 225 people out of 300 respondents stated that they did not vote for female legislative candidates in the 2019 election due to the strong patriarchal culture in the three districts, as well as the lack of popularity of female candidates due to their lack of activity in public spaces thus far. Another factor is women's low participation in party membership; political careers are viewed as more appropriate to pursue if they begin as partisan party cadres.